S kolesom prek meja - Kos, Jože (Urbani izziv, 1999)
The article describes the intent and content of the international Velo-City conference 1999, Maribor-Gradc and the organisation of this cycling development planning meeting. It focuses on the resolution of the conference concernig cycling traffic policies, the emerging network of European cycling connections and the traffic planning workshop about the difficult square in Maribor. The content framework of particular papers is shown, as well as other post-conference events. In the conclusion certain useful addresses for obtaining added data on sustainable traffic planning are given.
Keywords: kolesarjenje; kolesarske poti; kolesarski promet; planiranje; prometna politika